CTDBT Instruments to Measure The Critical Thinking Disposition Based on Gender in Biology Education Student - Jayanti Syahfitri; Harry Firman (Postgraduate, University of Mataram, 2022)
Critical thinking disposition is an important part of someone's critical thinking. This study aims to determine the differences in critical thinking dispositions of students in biology education based on gender. This research was conducted at Muhammadiyah of Bengkulu University involving 73 biology students as respondents, which is consisting of 19 male and 54 female. This research is a quasi-experimental type with one group. The instrument used in this study was the Critical Thinking Disposition in Biology Test (CTDBT), which is the first test instrument developed to see the critical thinking disposition in biology. The data obtained were analyzed through non-parametric statistics, namely the Mann-Withney test with the help of the SPSS version 20 application. The results showed that in general there was no significant difference in the disposition of biological critical thinking among male and female male and female students, except for the analyticity indicator. The results of this study can contribute to lecturers and stakeholders in making decisions to improve the quality of graduates at the University